2002
DOI: 10.1127/archiv-hydrobiol/154/2002/225
|View full text |Cite
|
Sign up to set email alerts
|

Macroinvertebrates colonising leaf litter of contrasting quality in a travertine Mediterranean stream

Abstract: We investigated the invertebrate assemblages that colonised two types of leaf litter bags, which differed considerably in quality: (I) Mixed-species bags made of leaves from indigenous tree and shrub species (Populus nigra L., Rubus ulmifolius SCHOTT. and Salix atrocinerea BROT.); (2) and bags made of the recalcitrant leaves from the exotic species Platanus orientalis L. The study was conducted at two sites differing in riparian canopy located in the Mediterranean stream Rio Vicario, charac terised by massive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In previous studies of detrital dynamics no relationship was evident between rates of leaf litter (CPOM) decomposition and the abundance of macroinvertebrates both in non-precipitating (Meyer, 1980;Stockley et al, 1998) and precipitating streams (Vivas & Casas, 2002). However, the sheer abundance of macroinvertebrates in moss mats (70000-700000 ind/m 2 according to Habdija et al (2004)) could also hinder the deposition of POM.…”
Section: Discussionmentioning
confidence: 86%
“…In previous studies of detrital dynamics no relationship was evident between rates of leaf litter (CPOM) decomposition and the abundance of macroinvertebrates both in non-precipitating (Meyer, 1980;Stockley et al, 1998) and precipitating streams (Vivas & Casas, 2002). However, the sheer abundance of macroinvertebrates in moss mats (70000-700000 ind/m 2 according to Habdija et al (2004)) could also hinder the deposition of POM.…”
Section: Discussionmentioning
confidence: 86%
“…Several studies investigated the breakdown of leaf litter in karst systems where tufa precipitates (CASAS and GESSNER 1999;VIVAS and CASAS, 2002;CASAS et al, 2006;CARTER and MARKS, 2007). These studies reported contradictory results: CARTER and MARKS (2007) reported significantly faster breakdown at the tufa site than at the site without tufa precipitation, while CASAS and GESSNER (1999) found tufa precipitation to impair decomposition.…”
Section: Introductionmentioning
confidence: 89%
“…In forested, perennial karst streams, the input of leaf litter could be a critical resource for the animal communities, as suggested for headwaters (Casas & Gessner, 1999). However, studies were carried out mainly in temperate regions (Vivas & Casas, 2002). In this study, we evaluated patterns of macroinvertebrate colonization during leaf litter decomposition in a tropical river.…”
mentioning
confidence: 98%